2001
DOI: 10.1117/1.1333676
|View full text |Cite
|
Sign up to set email alerts
|

Automated single-cell sorting system based on optical trapping

Abstract: We provide a basis for automated single-cell sorting based on optical trapping and manipulation using human peripheral blood as a model system. A counterpropagating dual-beam optical-trapping configuration is shown theoretically and experimentally to be preferred due to a greater ability to manipulate cells in three dimensions. Theoretical analysis performed by simulating the propagation of rays through the region containing an erythrocyte (red blood cell) divided into numerous elements confirms experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(74 citation statements)
references
References 37 publications
0
72
0
2
Order By: Relevance
“…The RBC's hemoglobins are known to absorb at 514.5 nm [4,5]. The intensity of the incident laser beam and the exposure time of cell suspensions were adjusted in such a way that the action of laser radiation by itself did not cause decomposition of RBC rouleaux and did not produce any pronounced photostress on RBCs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RBC's hemoglobins are known to absorb at 514.5 nm [4,5]. The intensity of the incident laser beam and the exposure time of cell suspensions were adjusted in such a way that the action of laser radiation by itself did not cause decomposition of RBC rouleaux and did not produce any pronounced photostress on RBCs.…”
Section: Methodsmentioning
confidence: 99%
“…The orientation of single RBC in two-beam traps has previously been described experimentally as well as theoretically by computer modeling based on individual beam effect [5]. Instead, we discuss RBC behavior under the influence of gradient dipole forces that result from interaction with the interference laser field.…”
Section: Orientation Of Rbc In the Fringes Of Interference Laser Fielmentioning
confidence: 99%
“…Efficient and rapid purification of cells has been accomplished with techniques such as fluorescence-activated cell sorting (FACS) (Ogawa et al 1994;Hulett et al 1973;Bonner et al 1972;Herzenberg and Sweet 1976;Assenmacher et al 1995;Johnson et al 2007), magnetic-activated cell separation (MACS) (Imamura et al 1995;Owen and Sykes 1984;Chalmers 2005, 2011), automated single-cell sorting using dual-beam optical trapping (Grover et al 2001), differential adhesion cell sorting (Hsu et al 2008), and disposable microfabricated fluorescence-activated cell sorting (lFACS) (Liu et al 2011;Yoon et al 2011;Azuma et al 2007). In addition, recent advancements in optofluidic flow cytometry, in which optics and microfluidics are used together to create novel functionalities on a small chip, hold great promise for lab-on-a-chip flow cytometry Hatayama et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the work of Grover et al who showed how optical tweezers can be applied in automated single cell-sorting using peripheral blood as a model system. 12 The erythrocytes were aligned into an upright position along the beam propagation. Trapped cells could then be recognized and sorted out by an imageprocessing system.…”
Section: Introductionmentioning
confidence: 99%